1999
DOI: 10.1161/01.atv.19.9.2199
|View full text |Cite
|
Sign up to set email alerts
|

Novel Effects of the Acyl-Coenzyme A:Cholesterol Acyltransferase Inhibitor 58-035 on Foam Cell Development in Primary Human Monocyte–Derived Macrophages

Abstract: Abstract-We examined the effect of acyl-coenzyme A:cholesterol acyltransferase (ACAT) inhibitors on intracellular cholesterol stores in primary human monocyte-derived macrophages (HMMs) during foam cell formation. HMMs were exposed to acetylated low density lipoprotein (acLDL, 500 g protein per mL) with or without 58-035 (1 to 10 g/mL) or CI-976 (2 g/mL) for 2 to 48 hours. Total cholesterol (TC) and esterified cholesterol (EC) mass was significantly lower while unesterified cholesterol (UC) increased slightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Thus, ER calcium depletion, which is an early event in macrophage FC loading, could be a key upstream event leading to macrophage death. Interestingly, Rodriguez and colleagues (63) have reported that macrophage-like cells derived from cultured human blood monocytes do not accumulate large amounts of FC and therefore, as expected, do not die when incubated with acetyl-LDL and an ACAT inhibitor. This finding is associated with a high level of cholesterol efflux and down-regulation of the scavenger receptor.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, ER calcium depletion, which is an early event in macrophage FC loading, could be a key upstream event leading to macrophage death. Interestingly, Rodriguez and colleagues (63) have reported that macrophage-like cells derived from cultured human blood monocytes do not accumulate large amounts of FC and therefore, as expected, do not die when incubated with acetyl-LDL and an ACAT inhibitor. This finding is associated with a high level of cholesterol efflux and down-regulation of the scavenger receptor.…”
Section: Discussionmentioning
confidence: 55%
“…Although we failed to detect cholesterol esterification activity, PfDGAT is highly homologous to the ACAT and DGAT families (2,12), and therefore, we treated P. falciparum-infected red cells with Sandoz 58-035 for 2 h at a concentration (10 g/ml) known to inhibit 99% of ACAT activity in mammalian cells (14,17). However, we failed to induce any change in the incorporation of [ 3 H]oleic acid into either TAG or its intermediates or show any deleterious effects on plasmodial growth (data not shown).…”
mentioning
confidence: 96%
“…The lipid (TC, FC, and TG) and protein concentrations of KV-LDL complex were similar to the corresponding concentrations of LDL. The KV-2920 concentration was 615.2 mg/ml, and the amount of KV-2920 contained in the KV-LDL complex was 800Ϯ40 mol/mol LDL (LDL molecular weight of 5.5ϫ10 5 based on the protein concentration). The electrophoresis pattern of the KV-LDL complex was the same as that of LDL (data not shown).…”
Section: Characteristics Of Ldl and Kv-ldl Complexmentioning
confidence: 99%
“…In fact, many studies have reported that an ACAT inhibitor prevents foam cell formation by macrophages and the development of atherosclerotic plaques. [5][6][7] However, most ACAT inhibitors have problems associated with low oral bioavailability and adrenal and/or hepatic toxicity. 8,9) In particular, adrenotoxicity is a major problem if an ACAT inhibitor is to be used in clinical situations.…”
mentioning
confidence: 99%